Novel approach to studying marine fauna: using long-life remote underwater video cameras to assess occurrence and behaviour of threatened and data-deficient elasmobranch species in southern Mozambique - Buschmann, Jule; Roques, Kim G.; Davies, Jaime S.; Dissanayake, Awantha; Keeping, Jennifer A. (Frontiers in Marine Science, 2024)
Understanding the behaviour and ecological role of elasmobranchs is essential for their conservation, particularly in regions harbouring threatened and data-deficient species like the Inhambane coastline in southern Mozambique, southwestern Indian Ocean. This study employed long-life remote underwater video cameras (LL-RUV) to observe elasmobranch occurrence and behaviour at a rocky reef near Praia do Tofo known for frequent elasmobranch sightings. Between 2021 and 2024, 524 hours of LL-RUV data were collected, revealing the presence of 14 threatened and data-deficient elasmobranch species. Reef manta rays (Mobula alfredi), small eye stingrays (Megatrygon microps), and oceanic manta rays (Mobula birostris) were identified as the primary elasmobranch users of the studied cleaning stations (n = 81, n = 72 and n = 61 respectively), engaging in mutualistic interactions with cleaner fish and spending significant amounts of time at the studied reef. In contrast, spotted eagle rays (Aetobatus ocellatus) and blacktip sharks (Carcharhinus limbatus) were solely observed cruising over the reef without engaging in cleaning interactions (n = 40 and n = 27 respectively). In addition, this study provides evidence of intra- and inter-specific interactions between reef and oceanic manta rays, small eye stingrays and bowmouth guitarfish (Rhina ancylostoma) and co-occurrences of both manta ray species and smalleye stingrays with “hitchhiker” species including cobia (Rachycentron canadum) and remoras (Echeneis spp.). The use of LL-RUV cameras represents a significant advancement in marine research. These cameras enable continuous, non-intrusive, long-term monitoring of marine environments, capturing natural behaviours, while minimising disturbances caused by divers. As a result, more accurate observations of elasmobranch behaviour and cleaning station dynamics can be recorded, which might be missed during short-term surveys. This research highlights the potential of LL-RUV cameras as powerful tools for advancing our understanding of elasmobranch occurrence and behaviour and underscores their value in informing targeted and effective conservation strategies. Beyond elasmobranch research, LL-RUVs hold tremendous potential for studying a wide range of marine species and habitats, offering a versatile tool for ecological monitoring and conservation efforts across diverse marine ecosystems.